Palladium-catalyzed asymmetric formal [3+2] cycloaddition of α-N-heterocyclic acrylates with vinyl epoxides for construction of isonucleoside analogs. Issue 90 (25th October 2019) - Huang, Ke-Xin; Xie, Ming-Sheng; Wang, Dong-Chao; Sang, Ji-Wei; Qu, Gui-Rong; Guo, Hai-Ming
Abstract : A highly efficient Pd-catalyzed asymmetric formal [3+2] cycloaddition of α-N-heterocyclic acrylates with vinyl epoxides has been developed for the first time. Abstract : A highly efficient Pd-catalyzed asymmetric formal [3+2] cycloaddition using α-N-heterocyclic acrylates to react with vinyl epoxides has been achieved for the first time to access chiral functionalized tetrahydrofuran skeletons (34 examples, up to 93% yield, >20 : 1 dr and 99% ee). Meanwhile, using a palladium/( S, S )- t Bu-FOXAP ca t alyst or a palladium/( R )-Segphos catalyst, purine or pyrimidine isonucleoside analogs are constructed in high yields and stereoselectivity, respectively. The commercial availability of the catalysts, broad substrate scope and easy transformation of the products make this methodology an attractive method in asymmetric synthesis.